Empire and Elites after the Muslim Conquest - Asma Barlas (International Institute of Islamic Thought, 2003)
Perhaps one would not expect a history of “Islamic rule” in the seventh and eighth centuries in what is now the Middle East to illuminate any contemporary debate on Islam, in particular about whether there is an innate civilizational clash between it and the (Christian) West. And yet this modest study manages to do that, if only tangentially and coincidentally, and if read with some reservations. Cambridge historians are renowned for their preoccupation with elites, generally of provinces far removed from the centers of power, and hence their single-minded focus on the “politics of notables” of relatively minor localities. From such provincial concerns, however, emerge more universal claims about, for instance, the nature of British colonial rule in India or of Islamic rule in the Middle Ages. Chase Robinson, following this tradition, assesses – as “critic and architect” – the changing status of Christian and Muslim elites following the Muslim conquest of northern Mesopotamia. Three themes are implicit: the interrelationship of history and historiography, the effects of the Muslim conquest, and the nature of Islam. Thus, I will review it thematically as well. I should point out that I engage his work as a generalist, not as a historian, and that I am interested not so much in his retelling of events as in the political meanings with which he endows them. (Re)writing History. To reconstruct a past about which there is such a dearth of primary period sources is at best hazardous. For one, where documents such as conquest treaties exist, they have little truth-value, says Robinson. He thus specifies that he is concerned less with their accuracy than with how they were perceived to have governed relations between local Muslims/imperial authorities, on the one hand, and Christians on the other. For another, conquest history in fact “describes post-conquest history.” Thus the “conquest past” is a re-presentation of events from a post-conquest present, an exercise in which Christians and Muslims had an equal stake since the “conquest past could serve to underpin [their] authority alike.” Historians then must disentangle events from their own narration, or at least recognize the ways in which recording events also reframes them. Fortunately for him, says Robinson, his work was enabled by that of al- Azdi, a tenth-century Muslim historian. However, even as he admits that ...